SERVICE PROVIDING ENTERPRISES IN ROMANIA - Rabontu, Cecilia – Irina; Babucea, Ana – Gabriela (European Scientific Journal, ESJ, 2014)
Service enterprises became important with the development of the tertiary sector in Romania which has recently become the predominant sector holding a share higher than 50% GDP. The specificity of these companies contribute in a sustainable way to the evolution of the number but also the turnover within the economy. Heterogeneity of services with the other main characteristics of the services put their mark on service enterprises transposing them an extremely high variability given the typology of services. The purpose of this paper is to provide an analysis of the evolution of service enterprises in the 1997-2013 time frame in order to establish the trend that these companies followed but also to establish a hierarchy of services depending on thnumber of companies provided. We have to considerboth the commercial and social enterprises and we will use statistical data provided by the NIS but also the studies on this subject so far. Our ultimate objective is to determine the evolution of service businesses in Romania and to extract the causes that have led to this development.